Prologue to the WISA 2008 Conference Special Edition - Jacobs, H E (Water S. A., 2009)
The Water Institute of Southern Africa (WISA) held its first conference in 1989 in Cape Town. The most recent and 10th Biennial WISA Conference was held in May 2008 at Sun City, South Africa. The WISA 2008 conference theme, 'Confluence of the Water Industry' set the scene for a wide range of presentations with regards to the South African water industry and research in related fields. In keeping with the conference theme this introduction provides a confluence of papers in this journal edition. A brief description of the paper selection procedure is included and each of the papers in this edition of the journal is purposefully referenced in this coherent text. [PUBLICATION ABSTRACT]